2014
DOI: 10.1108/amhid-03-2013-0016
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the prevalence of aggressive behaviour reported by Registered Intellectual Disability Nurses in residential intellectual disability services: an Irish perspective

Abstract: Purpose -Despite the high incidence of aggressive behaviours among some individuals with intellectual disability, Ireland has paid little attention to the prevalence of aggressive behaviours experienced by Registered Intellectual Disability Nurses (RNID). Within services the focus is mainly on intervention and management of such behaviours. Therefore a disparity occurs in that these interventions and management strategies have become the exclusive concern. Resulting in aggressive behaviour being seen as a sole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Two of the determinants of inequity and health disparities articulated in Table 1 considered the concept of health-damaging behaviour, and according to Emerson (2005), two-thirds of people with intellectual disability present with some form of challenging or self-injurious behaviour therefore are considered health damaging. Furthermore, Crotty et al (2014) found prevalence rates of aggression against property and aggression against others which can cause harm to be 48.9% and 50.7%, respectively, within the intellectual disability community. Considering this, these specific behaviours place people within a culture.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two of the determinants of inequity and health disparities articulated in Table 1 considered the concept of health-damaging behaviour, and according to Emerson (2005), two-thirds of people with intellectual disability present with some form of challenging or self-injurious behaviour therefore are considered health damaging. Furthermore, Crotty et al (2014) found prevalence rates of aggression against property and aggression against others which can cause harm to be 48.9% and 50.7%, respectively, within the intellectual disability community. Considering this, these specific behaviours place people within a culture.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of care in the community for people with intellectual disability and challenging behaviour has raised concerns regarding inadequate primary care services, health disparities and inequitable cultural care (Crotty et al, 2014; Parrish and Birchenall, 1997). Members of the primary healthcare and community nursing teams have expressed a need for expertise and further training in the area of intellectual disability and its’ associated behaviours (Aspray, 1999; Crotty et al, 2014; Duff et al, 2000; Lakhani and Bates, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estimates of the prevalence of aggression among individuals with intellectual disability, including those with mild or borderline intellectual disability (MBID), have reported that as many as 20% may engage in some form of aggression (Davies & Oliver, 2013;Lundqvist, 2013). Verbal and physical aggression are the most frequently reported typologies and are the leading cause for treatment referral in this population (Crotty, Doody, & Lyons, 2014). Both severe physical aggression that may result in bodily injury as well as milder forms of aggression (verbal threats) have the potential to adversely affect the individual with MBID, their family and support staff by leading to isolation, stigmatisation, resource drain and mental health sequela (Hensel, Lunsky, & Dewa, 2014;Woods & Ashley, 2007).…”
mentioning
confidence: 99%